Disclosure and subsequent innovation: Evidence from the patent depository library program - Jeffrey L. Furman; Markus Nagler; Martin Watzinger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
How important is information disclosure through patents for subsequent innovation? To answer this question, we examine the expansion of the USPTO Patent Library system after 1975. Before the Internet, patent libraries gave inventors access to patent documents. We find that after patent library opening, local patenting increases by 17% relative to control regions. Additional analyses suggest that the disclosure of technical information is the mechanism underlying this effect: inventors start to cite more distant prior art and the effect ceases after the introduction of the Internet. Our analyses thus provide evidence that disclosure plays an important role in cumulative innovation.
Keywords: 330